A haar wavelet series solution of heat equation with involution - Saparova, Burma; Mamytova, Roza; Kurbanbaeva, Nurjamal; Ahmedov, Anvarjon A. (Akademi Baru, 2021)
It is well known that the wavelets have widely applied to solve mathematical problems connected with the differential and integral equations. The application of the wavelets possess several important properties, such as orthogonality, compact support, exact representation of polynomials at certain degree and the ability to represent functions on different levels of resolution. In this paper, new methods based on wavelet expansion are considered to solve problems arising in approximation of the solution of heat equation with involution. We have developed new numerical techniques to solve heat equation with involution and obtained new approximative representation for solution of heat equations.